Effect of Smoking on the Composition of Erythrocyte Membrane Phospholipids - Toker, M.; Yilmaz, N.; Aktas, M. (Asian Journal of Chemistry, 2016)
In this study, the effect of cigarette smoking on the composition of erythrocyte membrane cholesterol and phospholipids was studied. Three groups were formed as control, working in cigaratee factory but not smoking and working in cigarette factory and smoking. The membrane phospholipids were separated from each other with thin layer chromatography (TLC). The phosphatidyl choline (PC), phosphatidyl ethanolamine (PE), phosphatidyl serine (PS) and sphingomyelin (SM) amounts for each group were measured as per cent. The ratios for sphingomyelin/phosphatidyl choline and total cholesterol/total phospholipids were also determined in per cent. The results showed that the amounts of phosphatidyl serine and sphingomyelin with ratio for total cholestrol/total phospholipid, and for sphingomyelin/phosphatidyl choline (PC) were increased significantly in smokers compared to control group and non-smokers at p < 0.05 level. Phosphatidyl choline and phosphatidyl ethanolamine decreased significantly in smokers at the p < 0.05 level. Increases in the ratios for total cholesterol/total phospholipids and sphingomyelin/phosphatidyl choline in smokers may be attributed to the alteration effect of cigaratte on erythrocyte membranes of those taking place in this group.